2020
DOI: 10.1111/jgs.16395
|View full text |Cite
|
Sign up to set email alerts
|

Improving Drug Therapy for Patients With Life‐Limiting Illnesses: Letʼs Take Care of Some Low Hanging Fruit

Abstract: This Editorial comments on the article by https://doi.org/10.1111/jgs.16335 et al., https://doi.org/10.1111/jgs.16336 et al., https://doi.org/10.1111/jgs.16360 et al., https://doi.org/10.1111/jgs.16370 et al., https://doi.org/10.1111/jgs.16241 et al. and https://doi.org/10.1111/jgs.16346 et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…An important opportunity during the pandemic is to implement strategies to reduce polypharmacy and inappropriate medications, especially in residents with life-limiting illnesses using evidence-based and expert-recommended guidance. [71][72][73] Reducing polypharmacy will not only reduce adverse events, it will also reduce staff time in medication administration, monitoring and documentation, and minimize interactions during which the virus transmission can occur.…”
Section: Clinical Carementioning
confidence: 99%
“…An important opportunity during the pandemic is to implement strategies to reduce polypharmacy and inappropriate medications, especially in residents with life-limiting illnesses using evidence-based and expert-recommended guidance. [71][72][73] Reducing polypharmacy will not only reduce adverse events, it will also reduce staff time in medication administration, monitoring and documentation, and minimize interactions during which the virus transmission can occur.…”
Section: Clinical Carementioning
confidence: 99%
“…In addition, FS monitoring increases staff burden and staff‐resident contacts, which would be especially detrimental in the current severe acute respiratory syndrome coronavirus 2 pandemic. Thus, decreasing FS monitoring may represent “low hanging fruit”: a relatively straightforward change that may provide substantial benefits to NH residents 12,13 …”
Section: Introductionmentioning
confidence: 99%
“…24 Simplifying glycemic regimens and reducing unnecessary fingersticks represents a "low-hanging fruit" intervention that can reduce treatment burden and may improve resident well-being. 25 The primary strength of our study is that it is the first to examine fingerstick frequency stratified by cognitive impairment status across NHs nationally. Individuals with moderate/severe cognitive impairment represent an important subgroup at high risk for adverse events and are increasingly becoming a focus for deprescribing interventions.…”
Section: Discussionmentioning
confidence: 99%
“…One previous study found that short‐acting insulin can safely be substituted with oral and long‐acting insulin in older adults with diabetes 24 . Simplifying glycemic regimens and reducing unnecessary fingersticks represents a “low‐hanging fruit” intervention that can reduce treatment burden and may improve resident well‐being 25 …”
Section: Discussionmentioning
confidence: 99%